Mapping Service Performance and Communication Patterns in the Networked Coffee Shop Community in Jember Regency - Erlambang Budi Darmanto; Luh Putu Suciati; Mohammad Adenan; Yunita Satya Pratiwi; Erman Arif; Doni Waluyo; Fadiatul Ismaniah (Alliance of Health Activists (AloHA), 2023)
Jember Regency is one of the coffee center areas in East Java. The increasing consumption of coffee has led to the proliferation of coffee shops in the Jember Regency. The importance of a relationship for a coffee shop or shop will facilitate the dissemination of information about the current development of coffee. Forum Barista Nusantara is a networked coffee community as a forum for coffee shops/shops to serve and mix coffee according to their respective competencies. This study aims to obtain data, process, and analyze mapping service performance and communication patterns in the networked coffee shop community in Jember Regency. The research method used is the analytical descriptive method. Data analysis techniques use spatial analysis and analysis of nearby neighbors as well as analysis of communication patterns. The results showed that in the Spatial Distribution of networked coffee shops in the Jember Regency there were 40 samples of shops spread across the Jember Regency. The performance of coffee shop services based on ratings on Google Maps shows that coffee shops in the Sumbersari District area have good performance with an average performance rating of 4.5-5 stars. The distribution pattern of coffee shops in Jember Regency through the analysis of nearby neighbors processed from QGIS software version 3.16 can be known to tend to group (cluster) because the distance between one coffee shop and another coffee shop is close together. Keywords: communication patterns; coffee shops; spread; networking